How Individuals With Down Syndrome Process Faces and Words Conveying Emotions? Evidence From a Priming Paradigm - Roch, Maja; Pesciarelli, Francesca; Leo, Irene (Frontiers in Psychology, 2020)
Emotion recognition from facial expressions and words conveying emotions is considered crucial for the development of interpersonal relations (Pochon and Declercq, 2013). Although Down syndrome (DS) has received growing attention in the last two decades, emotional development has remained underexplored, perhaps because of the stereotype of high sociability in persons with DS. Yet recently, there is some literature that is suggesting the existence of specific deficits in emotion recognition in DS. The current study aimed to expand our knowledge on how individuals with DS process emotion expressions from faces and words by adopting a powerful methodological paradigm, namely priming. The purpose is to analyse to what extent emotion recognition in DS can occur through different processes than in typical development. Individuals with DS (N = 20) were matched to a control group (N = 20) on vocabulary knowledge (PPTV) and non-verbal ability (Raven’s matrices). Subsequently a priming paradigm was adopted: stimuli were photos of faces with different facial expressions (happy, sad, neutral) and three words (happy, sad, neutral). On a computer screen the first item (face or word) was presented for a very short time (prime) and afterward a stimulus (face or word) appeared (target). Participants had to recognize whether the target was an emotion (sad/happy) or not (neutral). Four prime-target pairs were presented (face-word; word-face; word-word; face-word) in two conditions: congruent (same emotion prime/target) and incongruent (different emotion prime/target). The results failed to show evidence for differential processing during emotion recognition between the two groups matched for verbal and non-verbal abilities. Both groups showed a typical priming effect: In the incongruent condition, slower reaction times were recorded, in particular when the target to be recognized is the face, providing evidence that the stimuli were indeed processed. Overall, the data of the current work seem to support the idea of similar developmental trajectories in individuals with DS and TD of the same verbal and non-verbal level, at least as far as the processing of simple visual and linguistic stimuli conveying basic emotions is concerned. Results are interpreted in relation to recent finding on emotion recognition from faces and words in DS.